(untitled) (Annals of the University of Bucharest. Philosophy Series, 2025)
The author deals with the consideration of what he calls the post-metaphysical complex of the technosphere, for which the ontogenetic framework of classical metaphysics from Aristotle to Hegel is no longer valid. Instead, the question of the essence of man posits his transcendence in the emergence of Homo kybernetes, with which he removes the posthuman condition. To explain how the permeation of human and non-human appears in all areas of contemporary life as a connection and relationship of information, feedback, control and communication, it seems necessary to open the issue of the cyborgization of life itself. At the same time, the analysis of transhumanism in the opinion of Stefan Lorenz Sorgner proves to be stimulating for understanding what the digital age of the technosphere presupposes, and that is the question of the possibilities of freedom beyond its metaphysical framework as it was considered in the speculative thinking by Schelling. Instead of freedom as absolute, the time has come to establish the possibility of thinking about freedom as an experiment of thought and action beyond human reduction and its associated anthropologies that have lost their credibility in an encounter with the complexity of Homo kybernetes.